2019
DOI: 10.3390/agriculture9120260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutritional Management on Available Mineral Nitrogen and Soil Quality Properties in Coffee Agroecosystems

Abstract: Coffee crop management is guided by an approach of synthetic nitrogen fertilizers application in order to guarantee high production rates; however, this type of management increases soil degradation. A study was conducted in order to evaluate the impact of changing soil nutritional management from Chemical (NPK) to Organic (Farmyard Manure-FYM), and from Chemical (NPK) to Mixed (NPK + FYM) regarding soil quality properties and mineral nitrogen available in coffee agroecosystems; a multi-spatial analysis was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The soil organic carbon measurements in this study align with those reported by Kurniawan et al (2021), that the application of organic fertilizer alone or in combination with NPK fertilizer can increase soil organic carbon. The results of Olaya et al (2019) also showed that organic fertilizers sourced from manure have the potential to boost the buildup of soil organic carbon, resulting in alterations in the microbial community structure and promotion of microbial biomass.…”
Section: Soil Organic Carbon Mattermentioning
confidence: 96%
“…The soil organic carbon measurements in this study align with those reported by Kurniawan et al (2021), that the application of organic fertilizer alone or in combination with NPK fertilizer can increase soil organic carbon. The results of Olaya et al (2019) also showed that organic fertilizers sourced from manure have the potential to boost the buildup of soil organic carbon, resulting in alterations in the microbial community structure and promotion of microbial biomass.…”
Section: Soil Organic Carbon Mattermentioning
confidence: 96%